Glutenin analysis for the safe screening of self-pollinated wheat seeds when developing doubled-haploid populations - Torres, Gisele Abigail Montan; Scagliusi, Sandra Maria Mansur; Chaves, Márcia Soares; Consoli, Luciano (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to apply glutenin analysis, as a simple and reliable method, to identify self-pollinated wheat (Triticum aestivum) seeds in F1 crosses, when developing mapping populations using doubled-haploid (DH) technology. F1 seeds were subjected to glutenin analyses using gel electrophoresis to verify and confirm their heterozygotic profiles. Glutenin analyses were carried out using one half of the endosperm of each of the 87 F1 seeds. The other half of the endosperm was used to develop the mapping population through DHs. Plants with band patterns different from the expected ones were discarded. Although the incidence of self-pollinated seeds was relatively low (only 8%), the screening of F1 heterozygotic profiles is extremely important, particularly when creating reliable mapping populations.